The Effectiveness of Problem-Based Learning Strategies and Integrity Values in Anti-Corruption Education in Higher Education - Istikayati, Sri Nur; Wayanti, Sri; Rodiyatun, Rodiyatun (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study explores the effectiveness of Problem-Based Learning (PBL) strategies and the integration of integrity values in anti-corruption education within higher education institutions. The primary objective is to assess how these pedagogical approaches contribute to the development of ethical awareness and anti-corruption attitudes among university students. By utilizing a qualitative literature review method, this research synthesizes existing studies, articles, and academic papers that examine the intersection of PBL and integrity in anti-corruption education. PBL, with its emphasis on real-world problem-solving and active student engagement, is shown to promote critical thinking and ethical decision-making, which are crucial in understanding and combating corruption. The incorporation of integrity values within the curriculum further strengthens students' commitment to ethical behavior and social responsibility. Findings suggest that PBL not only enhances learning outcomes but also instills a deeper understanding of the importance of integrity in the fight against corruption. Moreover, the study identifies key factors that influence the effectiveness of these strategies, including faculty training, student participation, and institutional support. This paper concludes with recommendations for higher education institutions to implement PBL strategies and embed integrity values to foster a generation of students equipped to challenge corruption in their professional and personal lives.